Excitotoxic lesions in the central nucleus of the amygdala attenuate stress-induced anxiety behavior - Ventura-Silva, Ana Paula; Melo, António; Ferreira, Ana Catarina; Carvalho, Miguel Murteira; Campos, Filipa Lopes; Sousa, Nuno; Pêgo, José M. (Frontiers in Behavioral Neuroscience, 2013)
The extended amygdala, composed by the amygdaloid nuclei and the bed nucleus of the stria terminalis (BNST), plays a critical role in anxiety behavior. In particular, the link between the central nucleus of the amygdala (CeA) and the BNST seems to be critical to the formation of anxiety-like behavior. Chronic unpredictable stress exposure is recognized as a validated animal model of anxiety and is known to trigger significant morphofunctional changes in the extended amygdala. Quite surprisingly, no study has ever analyzed the role of the CeA in the onset of stress-induced anxiety and fear conditioning behaviors; thus, in the present study we induced a bilateral excitotoxic lesion in the CeA of rats that were subsequently exposed to a chronic stress protocol. Data shows that the lesion in the CeA induces different results in anxiety and fear-behaviors. More specifically, lesioned animals display attenuation of the stress response and of stress-induced anxiety-like behavior measured in the elevated-plus maze when compared with stressed animals with sham lesions. This attenuation was paralleled by a decrease of stress-induced corticosterone levels. In contrast, we did not observe any significant effect of the lesion in the acoustic startle paradigm.. As expected, lesion of the CeA precluded the appearance of fear behavior in a fear-potentiated startle paradigm in both non-stressed and stressed rats. These results confirm the implication of the CeA in fear conditioning behavior and unravel the relevance of this brain region in the regulation of the HPA axis activity and in the onset of anxiety behavior triggered by stress.